2010
DOI: 10.1002/bdrb.20234
|View full text |Cite
|
Sign up to set email alerts
|

The cynomolgus monkey as a model for developmental toxicity studies: variability of pregnancy losses, statistical power estimates, and group size considerations

Abstract: For designing and managing primate developmental toxicity studies, this type of analysis provides an objective tool to facilitate decisions either by supplementing groups with additional pregnant animals or stopping a group because an adverse effect on offspring survival has already been adequately revealed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 28 publications
0
37
0
Order By: Relevance
“…An earlier review of the cynomolgus monkey reported abortion rates between 11.7% and 30.2% [54], which seem comparable to more recent observations of 8.8-20.3% cumulative prenatal loss rates [9]. In the context of developmental toxicity evaluation, however, it is important to recognize that-unlike cumulative loss rates-prenatal loss rates among vehicle groups in single studies can be highly variable and range from zero to >40% [28]. Early losses can be difficult to interpret, in part because the GD 18-20 pregnancy is typically diagnosed by the presence of a gestational sac, yet a fetal heartbeat cannot be visualized until 1-2 weeks later.…”
Section: Developmental Toxicity Studiesmentioning
confidence: 51%
See 3 more Smart Citations
“…An earlier review of the cynomolgus monkey reported abortion rates between 11.7% and 30.2% [54], which seem comparable to more recent observations of 8.8-20.3% cumulative prenatal loss rates [9]. In the context of developmental toxicity evaluation, however, it is important to recognize that-unlike cumulative loss rates-prenatal loss rates among vehicle groups in single studies can be highly variable and range from zero to >40% [28]. Early losses can be difficult to interpret, in part because the GD 18-20 pregnancy is typically diagnosed by the presence of a gestational sac, yet a fetal heartbeat cannot be visualized until 1-2 weeks later.…”
Section: Developmental Toxicity Studiesmentioning
confidence: 51%
“…Per ICH M3(R2), evaluation of fertility is typically required before initiating phase III trials and/or conducted in parallel with phase II trials. Whereas the guidelines recommend physical mating for evaluation of fertility, this is not being done routinely in NHPs for two main reasons: (1) Typically, fertility rates in macaques are clearly <100% (typically 25-45% per cycle and approximately 60% per animal, preimplantation losses are around 25%) [27], and prenatal losses can be as high as 40% [9,28] and (2) While evaluation of implantation sites is a hallmark of rodent fertility studies, this normal fertility end point is not meaningful in macaques, in which there is normally a single implantation site that is then often lost shortly after implantation. Twin pregnancies/births are extremely rare in macaques, with an overall incidence of twin live births around 0.1% [29,30].…”
Section: Fertility and Early Embryonic Development Studymentioning
confidence: 99%
See 2 more Smart Citations
“…The duration of the postnatal phase will be dependent on which additional end-points are considered relevant for the pharmacological activity. The numbers of confirmed pregnant cynomolgus monkeys per group should be sufficient to detect threefold increase in pregnancy/ parturition-associated losses with 80% power with 95% confidence interval (Jarvis et al, 2009). The sponsor should justify the study design if other NHP species are used.…”
Section: Biotechnology-derived Productsmentioning
confidence: 99%